Lipoblastoma-Like Tumor and Fibrosarcoma-Like Lipomatous Neoplasm Represent the Same Entity: A Clinicopathologic and Molecular Genetic Study of 23 Cases Occurring in Both Men and Women at Diverse Locations - Gross, John M; Perret, Raul; Coindre, Jean Michel; Le Loarer, Francois; Michal, Michael; Michal, Michal; Miettinen, Markku; McCabe, Chantal E; Nair, Asha A; Swanson, Amy A; Thangaiah, Judith J; Torres-Mora, Jorge; et al. (Modern pathology, 2023)
Lipoblastoma-like tumor (LLT) is a benign soft tissue tumor demonstrating mixed morphologic features of lipoblastoma, myxoid liposarcoma, and spindle cell lipoma but lacking genetic alterations associated with those tumors. LLT was originally thought to be specific to the vulva but has since been reported in the paratesticular region. The morphologic features of LLT overlap with those of "fibrosarcoma-like lipomatous neoplasm" (FLLN), a rare, indolent adipocytic neoplasm considered by some to form part of the spectrum of atypical spindle cell and pleomorphic lipomatous tumor. We compared the morphologic, immunohistochemical, and genetic features of 23 tumors previously classified as LLT (n = 17) and FLLN (n = 6). The 23 tumors occurred in 13 women and 10 men (mean age, 42 years; range, 17 to 80 years). Eighteen (78%) cases arose in the inguinogenital region, whereas 5 tumors (22%) involved noninguinogenital soft tissue, including the flank (n = 1), shoulder (n = 1), foot (n = 1), forearm (n = 1), and chest wall (n = 1). Microscopically, the tumors were lobulated and septated, with variably collagenized fibromyxoid stroma, prominent thin-walled vessels, scattered univacuolated or bivacuolated lipoblasts, and a minor component of mature adipose tissue. Using immunohistochemistry, 5 tumors (42%) showed complete RB1 loss, with partial loss in 7 cases (58%). RNA sequencing, chromosomal microarray, and DNA next-generation sequencing study results were negative for significant alterations. There were no clinical, morphologic, immunohistochemical, or molecular genetic differences between cases previously classified as LLT or FLLN. Clinical follow-up (11 patients [48%]; range, 2-276 months; mean, 48.2 months) showed all patients were alive without disease, and only one patient had experienced a single local recurrence. We conclude that LLT and FLLN represent the same entity, for which "LLT" seems most appropriate. LLT may occur in either sex and any superficial soft tissue location. Careful morphologic study and appropriate ancillary testing should allow for the distinction of LLT from its potential mimics.
Keywords: liposarkom; Humans; Lipoblastoma; myxoidní liposarkom; Biomarkers, Tumor; Liposarcoma, Myxoid; Female; dospělí; myxoid sarcoma; lidé; fibrosarcoma-like lipomatous neoplasm; Liposarcoma; molekulární biologie; lipoblastoma-like tumor; nádorové biomarkery; Adult; ženské pohlaví; fibrosarkom; Male; lipomatous tumor; lipoblastom; Fibrosarcoma; mužské pohlaví; Molecular Biology; lipom; Lipoma